(untitled) (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2022)
XYZ Company is a company engaged in the property sector. Inventory data processing applied to this company is still manual, such as recording and managing inventory data using the Microsoft Excel application which produces unstructured output and makes it difficult to find data if the amount is large. What usually happens when processing data using Microsoft Excel is that there is duplication of data, both intentional and unintentional. From the problem of asset data management that is lacking, it is necessary to design an information system for managing asset data at company XYZ. The design is done by conducting a needs analysis followed by system design. The results of the analysis of user needs, there are three users of information system assets, namely admin, supervisor, and staff. The design is based on user needs analysis by designing Data Flow Diagrams and Entity Relationship Diagrams, database design, and website-based information system interface design. Interface design includes designing the main page interface, designing the admin page interface, designing the supervisor interface, designing the staff page interface, designing the added asset page out, designing the incoming asset page interface, the incoming and outgoing inventory page interface, the added user page interface. With this design, the company has an overview of the information system that will be built and adjusts to needs.